Flibanserin for Hypoactive Sexual Desire Disorder: An Open-Label Safety Study. Issue 3 (1st March 2018) - Simon, James A.; Derogatis, Leonard; Portman, David; Brown, Louise; Yuan, James; Kissling, Robert
Abstract: Background: To evaluate the safety of flibanserin in premenopausal and naturally postmenopausal women with hypoactive sexual desire disorder (HSDD) in an open-label extension (OLE) study. Aim: To examine the safety and tolerability of flibanserin 100 mg once daily at bedtime in the treatment of premenopausal and naturally postmenopausal women with HSDD in a multicenter 28-week OLE study. Methods: Patients entering this study received flibanserin or placebo in the double-blinded, placebo-controlled trials of premenopausal and postmenopausal women and in a pharmacokinetic study of postmenopausal women. Outcomes: The primary end point of this OLE study was the incidence of adverse events (AEs). Secondary exploratory efficacy measures included the Female Sexual Distress Scale–Revised (FSDS-R) total score and FSDS-R item 13 (distress owing to low desire) score and the Female Sexual Function Index (FSFI) total score. Because the sponsor terminated the study early at discontinuation of the development of flibanserin, only descriptive statistics were calculated. Results: Of the 595 patients receiving study medication, 346 and 249 patients were premenopausal and postmenopausal, respectively. The mean number of days of exposure to flibanserin was 72.8 (SD = 41.6). AEs were reported by 352 patients (59.2%), and most AEs (93.8%) were mild or moderate. The most common AEs (≥5%) were dizziness (9.6%), somnolence (8.6%), insomnia (6.2%), and nausea (5.7%). There were no flibanserin-related serious AEs and no instances of suicidal ideation. The safety profile of flibanserin was similar for premenopausal and postmenopausal women. The FSDS-R total scores and FSDS-R item 13 scores were numerically lower at weeks 4, 12, and 20 than at baseline (decrease in distress owing to low desire) for premenopausal and postmenopausal women. Mean FSFI total scores were numerically higher at weeks 4, 12, and 20 than at baseline, irrespective of menopausal status of the patients. Clinical Implications: The results of this study support the safety and tolerability of flibanserin for the treatment of HSDD in premenopausal and naturally postmenopausal women. Strengths and Limitations: Although this open-label study was designed to be 28 weeks long, it was discontinued early by the sponsor, and patients' maximum duration of exposure to flibanserin was 23.9 weeks. The open-label design and lack of a placebo-controlled arm are other study limitations. Conclusion: In this open-label study, flibanserin 100 mg once daily at bedtime was generally safe and well tolerated by premenopausal and naturally postmenopausal women with HSDD.